Ethnography of Communication in Sundanese-Javanese Bicultural Society (A Study on the Adaptation of Javanese Migrant Society in Ciamis Regency, West Java Province-Indonesia) - Duddy Zein, Wagiati, Nani Darmayanti (International Journal of Advanced Science and Technology, 2020)
Ethnography of communication in Ciamis Regency shows the interesting symptoms both seen from the communication aspects or the others. This is caused by the condition of the society in Ciamis Regency, that is bicultural, namely Sundanese and Javanese. This condition caused the language used by the society becomes multilingual. This study examines the ethnography of communication in Sundanese-Javanese Bicultural Society in Ciamis Regency, West Java Province-Indonesia. This method used in this study is the descriptive-qualitative method. This study was conducted in three stages which are the data collection stage, the data analysis stage, and the data analysis results presentation stage. The analysis method used in this study is the qualitative method. This study was carried out in Ciamis Regency by choosing five districts as the observation sites which with the sites are determined by the wind direction. The sites are Sindangkasih District, Sukamantri District, Lakbok District, Banjarsari District, and Pamarican District. 30 people from various backgrounds scattered in those districts in Ciamis Regency were chosen as the informant. The research results show that (1) the interaction between Sundanese ethnic societies as the indigenous society, with Javanese ethnic society as the immigrant society occurred peacefully without horizontal conflict; (2) The mutual respect attitude between Sundanese ethnic societies and Javanese ethnic society is influenced by the cultural factors of the Sundanese ethnic society which put forward the attitude somѐah hadѐ ka sѐmah; (3) the interaction and communication between Sundanese and Javanese culture in Ciamis Regency is shown from several aspects, such as aspects of religion, aspects of marriage, aspects of language, and interethnic attitudes and behaviors.   Keywords — ethnography of communication, bicultural, Sundanese, Javanese, Ciamis Regency